Effect of phytase supplementation on performance, bone densitometry and carcass yield in broilers chicks - doi: 10.4025/actascianimsci.v33i3.10702 - Junqueira, Otto Mack; Duarte, Karina Ferreira; Assuena, Vinícius; Filardi, Rosemeire da Silva; Laurentiz, Antonio Carlos de; Praes, Maria Fernanda Ferreira Menegucci (Acta Scientiarum. Animal Sciences, 2011)
An experiment was conducted to evaluate the performance, bone densitometry and carcass yield of broilers chicks, using different levels of phytase enzyme. Nine hundred and sixty male one-day-old broiler chicks were used. The birds were distributed in a completely randomized experimental design, involving five treatments and six replications of 32 chicks each. The treatments consisted of a control diet for each phase, and four other diets were formulated adding growing levels of the phytase enzyme (250, 500, 750 and 1,000 FTU of phytase kg-1 feed). When adding the phytase enzyme, the nutritional matrix was valued to guarantee the same nutritional levels as the control diet. In general, the addition of phytase enzyme determined a linear decrease on the performance of the birds. However, the performance obtained with the level of 250 FTU phytase kg-1 feed were no different from the control treatment. The best bone density results were observed in the control treatment with no phytase, and the highest leg and thigh yield were obtained at the level of 514 FTU phytase kg-1.